Exploring Imperative Mood in the Movie Dora and the Lost City of Gold - Siti Waliyatus Saadah; Lusi Susilawati (Syntax Idea)
This study aims to analyze the use of imperative mood in the film "Dora and the Lost City of Gold". Descriptive qualitative method is used to analyze the data deeply and explain it descriptively. Data collection techniques used a combination of basic methods, namely observation, and advanced techniques, namely note-taking techniques. The syntactic approach is used to examine the structure of sentences, clauses, phrases, and word patterns in language. Data analysis techniques use qualitative analysis methods, including data condensation, data presentation, and conclusion drawing and verification. The findings of this study show that there are several forms of imperative mood, including Simple Imperative, Prohibitive Imperative, Let's Imperative, Polite Imperative, and Future Imperative. Data analysis shows that the most common form of imperative mood used in movies is Simple Imperative. The implication of these findings in theoretical and practical contexts is that the use of imperative mood in movies can provide insight into the relationship between language and culture. The contribution of this study to the field of research is to provide a better understanding of the use of imperative mood in movies, especially in the context of the movie "Dora and the Lost City of Gold".